The Role of NDRG2 in the Chronic Pain Process - Hao, Yue; Li, Zhaoshuang; Wen, Xinya; Zheng, Jin (Journal of Contemporary Medical Practice, 2024)
Chronic pain is an important physiological response of the organism that involves a variety of molecules and cells, among which astrocytes play an important role in the development of chronic pain. NDRG2, a member of the N-myc downstream regulatory gene family, is expressed in astrocytes of the central nervous system and is involved in physiological functions affecting apoptosis, astrocyte activation, blood-brain barrier integrity and glutamate clearance regulation of glutamate clearance and other physiological functions. In this paper, we focus on the involvement of NDRG2 in the regulation of chronic pain by affecting the function of astrocytes, and discuss whether NDRG2 can be used as a potential target for pain treatment, taking into account the existing studies.